Skin Development in H. huso Larvae - Fazel Shooraki, H.; Saadatfar, Z.; Shahsavani, D. (Journal of Morphological Sciences, 2018)
Introduction Fish skin is important for life and protection mechanisms. Sturgeon skin also has an economical potential for its leather.Materials and Methods This article is a light microscopy study for knowledge the development of epidermis and dermis in one species of sturgeon (Huso. huso). The fishes from different days of week-1 to week-6 were caught from Shahid Marjani propagation center and were processed.Results From 1(dph) the epidermis as two layers and dermis as a very thin collagen layer had formed. Sensory buds in epidermis and chromatophore cells in dermis of head and also arranged the dermal endothelial cells were features of 3 (dph). At 10 (dph) there was an increase in epidermal cell line, existence the circular cells as club cells in epidermis and increase in dermal thickness observed. From the character of 20 (dph) was organized epidermis to three layers and collagen fibrils as parallel to body. From 25- 40 (dph) an increase in cell lines of epidermis up to 10 rows in some areas was observed.Conclusion The most important changes were the events occurred in dermis. The self-organized collagen fibrils to several lamellae, invading the fibroblasts to derm and forms of stratum campactum and stratum spongiosum.
Keywords: huso huso; skin development; histolog